The Influence of Environmental Awareness, Peers, and Self-Efficacy on Sustainable Consumption Behavior - Rista Maulidina; Kardoyo (Journal of Economic Education, 2026)
Sustainable consumption behavior is an important aspect of environmental education. Although SMA Negeri 14 Semarang has implemented various environmental programs as an Adiwiyata Mandiri School, there remains a gap between students' understanding of sustainability and their consumption practices. This study aims to analyze the influence of environmental awareness, peer support, and self-efficacy on sustainable consumption behavior through behavioral intentions and to examine the role of perceived school support as a moderating variable. This study used a quantitative approach with a causal design. The sample size was 283 students selected using proportional stratified random sampling. Data were collected through questionnaires and analyzed using multiple linear regression and mediation and moderation tests with PROCESS Hayes. The results show that environmental awareness and peer support have a significant positive effect on sustainable consumption behavior, while self-efficacy and behavioral intentions do not have a significant direct effect. Environmental awareness, peers, and self-efficacy have a significant effect on behavioral intentions. Behavioral intentions mediate the relationship between the variables, while perceived school support moderates the relationship between behavioral intentions and sustainable consumption behavior. These findings enrich the study of sustainable consumption behavior and provide a basis for schools to strengthen the habit of sustainable consumption behavior in students.